Ergogênese alimentar: os riscos atrás dos mitos - Lara, Paola Aparecida Teixeira de; Burini, Roberto Carlos [UNESP]; Maestá, Nailza [UNESP] (My University, 2010)
The search for ergogenic resources for high performance has attracted the attention of the athletes since the sport became a vehicle of status and wealth. In this occupation, the ethics and legality have been backed by material values. In this sense, the sports and the media have gone out of step with science this rather concerned about the effectiveness of ergogenic aids and their biosafety to the health of users. Unfortunately, the authorities controlling the market of nutritional supplements (scientifically efficient), have been missing with regard to the quality of products available, which contaminants pose a health risk for users. Let there dishonesty of labeling and folk culture that "athlete does not fed, but supplements it" and that "if some is good more must be better. In addition, athletes are influenced by parents, coaches, competitors and high financial stakes to improve their performance. An association between individuals who use nutritional supplements that offer health risk represents an important opportunity for preventive counseling.

A busca de recursos ergogênicos ao alto rendimento tem atraído a atenção dos atletas desde que o esporte passou a ser veículo de status e riqueza. Neste mister a ética e a legalidade têm sido secundada pelos valores materiais e o meio esportivo e a mídia têm andado em descompasso com a ciência, esta sim preocupada com a eficácia dos ergogênicos e com sua biossegurança para a saúde dos usuários. Lamentavelmente, as autoridades controladoras do mercado de suplementos nutricionais (cientificamente eficazes) têm sido ausentes no que diz respeito à qualidade dos produtos disponíveis, cujos contaminantes colocam em risco a saúde dos usuários. Agravem-se a desonestidade do conteúdo dos rótulos e a cultura folclórica que “atleta não se alimenta, e sim se suplementa” e também que “se pouco é bom, mais deve ser melhor”. Além disso, os atletas são influenciados por pais, treinadores, competidores e pelas premiações das competições esportivas para melhorar seu desempenho. Uma associação entre indivíduos que usam suplementos nutricionais que oferecem risco à saúde representa uma oportunidade importante para a assistência preventiva.
Sports supplements: the risks behind the myths
Keywords: Food ergogênese; Myths and risks; Ergogênese alimentar; Mitos; Riscos